Freakonomics [videorecording (DVD)] : [the movie] - Gordon, Seth; Gibney, Alex; Grady, Rachel; Ewing, Heidi E.; Spurlock, Morgan, 1970-2024; Jarecki, Eugene; Levitt, Steven D.; Dubner, Stephen J. (Magnolia Home Entertainment, 2011)
The highly anticipated film version of the phenomenally bestselling book about incentives-based thinking by renowned economists Steven Levitt and Stephen Dubner. Like the book, the film examines human behavior with provocative and sometimes hilarious case studies, bringing together a dream team of filmmakers responsible for some of the most acclaimed and entertaining documentaries in recent years.